Partisipasi Generasi Muda dalam Pemilu 2024 di Kepulauan Riau - Hafifa, Nur; Umaira, Putri Nabilah; Febriansyah, M. Iqbal; Rafi’i, M. Tsaqif (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research analyzes the role of the younger generation in the 2024 Election in the Riau Islands Province, with a focus on the Millennial Generation and Generation Z. Data from the KPU shows that voters in this province are dominated by young voters, consisting of 1,500,974 people with a total of 5,914 polling stations. Policies that are really needed by the people of the Riau Archipelago include attention to the archipelagic region, the fishing prof4ession and fisheries, which it is hoped can be accommodated through the Archipelagic Region Bill. Young generation participation factors in elections are influenced by the capability and relevance of candidates, openness and accountability in politics, media and political persuasion, national and global political context, as well as their perspective on political issues. Generation Z, as the largest first-time voters, plays an important role as influencers on social media, political volunteers, and mobilizers of online protest movements. This study highlights the importance of effective and relevant campaign strategies for the younger generation to increase their political participation and encourage positive change in the Riau Islands Province.